Complications of pregnancy and benign familial joint hyperlaxity. - Thornton, J G (1988)
A family is described in which four generations were affected by benign familial joint hyperlaxity and, in the two generations for which obstetric data were available, pregnancies were complicated by unexplained mid-trimester vaginal bleeding. This prompted a study to determine whether unexplained antepartum haemorrhage (APH) and premature rupture of the membranes (PROM) both of which might reflect the structure of fetal collagen, were associated with joint hyperlaxity in offspring. The joint hyperlaxity of children born from such pregnancies was slightly greater than that found in age matched children born from uncomplicated pregnancies.